Karakteristik Kepribadian Guru Pendidikan Agama Islam di SD Negeri 02 Indralaya - Zainuddin Zainuddin; Rizki Julinda (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
The teacher's personality is one of the important factors for the success of learning, especially Islamic Religious Education learning which contains many values ​​of faith and student behavior. Islamic education teachers become one of the important factors that can affect the success of education. Instilling faith and good morals, can only be done by teachers who have good personality. For this reason, this study aims to reveal how the personality that teachers should have, especially basic education teachers. The data collection in this study is observation, interviews, and documentation. The data collected were analyzed using data analysis including; data reduction, data presentation, and conclusion drawing. While the results of this study are; The personal characteristics of Islamic Religious Education teachers include; have good morals, discipline, and responsiveness. Besides that; 1) have a high concern for students by not discriminating against each other, acting fairly and not favoritism. 2) have firmness and authority, and compassion 3) have a good personality shown by behavior in accordance with Islamic values ​​(good morals).